Unintended consequences of quote limits policy on stock market dynamics: evidence from the MF-X-DMA analysis - Lv, Dayong; Zhou, Yaping; Zhang, Jiarui; Yin, Linsen (Frontiers in Physics, 2025)
IntroductionThis study investigates the effect of recently implemented quote limits policy in China’s A-share Main Board market, a mechanism designed to enhance market stability. We examine whether this policy achieves its goals uniformly across distinct large-cap (HS300) and mid-to-small cap (CSI500) market segments.MethodsUtilizing the Multifractal Detrending Moving Average Cross-Correlation analysis (MF-X-DMA) and the nonlinear Granger causality test, we assess the policy’s potential heterogeneous impact on these two indices.ResultsOur findings reveal that the policy decreases market efficiency and increases cross-market co-movement complexity for HS300, while conversely improving market efficiency and information flow for CSI500.DiscussionWe offer novel empirical evidence on this policy using nonlinear methods. Our findings highlight the potentially divergent and unintended consequences of “one-size-fits-all” financial regulations across varied market segments, providing valuable insights for policymakers.